Penguatan Pendidikan Karakter Berbasis Kolaborasi Untuk Meningkatkan Sikap Toleransi Dan Empati - Nurul Huda; Nurul Ayyami Shalehati (LP3M IAIFA Kediri, 2025)
Character education is a structured effort to instill moral values, ethics, and virtues in students as preparation for facing future challenges. The purpose of this study is to examine the importance of character education and the strategies for its implementation in enhancing tolerance and empathy within the school environment. The method used is the service-learning approach within a community engagement program to gain an in-depth understanding of how the integration of community service and learning can mutually reinforce one another and provide real benefits for students. The research design applied is Participatory Action Research (PAR). This approach enables researchers to collaborate directly with students in every stage of the research process, including planning, implementing activities, and evaluating the community service program. Overall, the findings indicate that the Service Learning approach is highly effective in shaping students’ attitudes of tolerance and empathy. The study shows that character education implemented through teacher role modeling, a positive school culture, and the integration of values into learning activities can significantly enhance students’ social attitudes and positive behaviors. Thus, character education plays a strategic role in developing a generation that is virtuous, possesses integrity, and is capable of contributing to society.